2007
DOI: 10.1080/10641950701521601
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thrombophilic Disorders and Type of Severe Early-Onset Hypertensive Disorder of Pregnancy

Abstract: In this population, the high prevalence of thrombophilic factors and chronic hypertension was confirmed. There were small differences between groups. Hereditary thrombophilic disorders were associated with fetal growth restriction but not with type of maternal disease, suggesting an effect on placental function. Maternal body mass index was lower in women with HELLP syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Sample size In all, 128 subjects were needed to detect a 50% reduction from a 35% recurrence rate of HD [1] (one‐tailed, power 80%). Two‐tailed calculations (sample size 262) were initially used, although not considered strictly necessary as no increase in HD and/or SGA infants was expected, nor any serious side effects of LMWH [16], and with the anticipation of sufficient recruitment, given an estimation of 1% severe HD of all pregnancies per year (180 000) in the Netherlands, 11–24% of which would have inherited thrombophilia [1,17]. The sample size was therefore recomputed using one‐sided testing.…”
mentioning
confidence: 99%
“…Sample size In all, 128 subjects were needed to detect a 50% reduction from a 35% recurrence rate of HD [1] (one‐tailed, power 80%). Two‐tailed calculations (sample size 262) were initially used, although not considered strictly necessary as no increase in HD and/or SGA infants was expected, nor any serious side effects of LMWH [16], and with the anticipation of sufficient recruitment, given an estimation of 1% severe HD of all pregnancies per year (180 000) in the Netherlands, 11–24% of which would have inherited thrombophilia [1,17]. The sample size was therefore recomputed using one‐sided testing.…”
mentioning
confidence: 99%
“…In 1980, Soulier and Boffa described an association between LAC and recurrent pregnancy loss (27), which was confirmed initially by case reports and later by clinical series associating aPL with (generally second‐trimester) pregnancy loss, fetal growth restriction, and severe preeclampsia (28). There is no consensus concerning which, if any, autoantibody profiles predict pregnancy outcome in women with aPL (4–14); in a recent retrospective analysis of 38 patients who were tested for LAC, aCL, and anti‐β 2 GPI it was argued that triple positivity is the best predictor (4, 5), whereas investigators from Saudi Arabia argued for (broadly defined) LAC positivity (14).…”
Section: Discussionmentioning
confidence: 91%
“…Yasuda et al [11] found similar results in 22 women with IUGR without preeclampsia, while another study did not find this association in 25 women [12]. Other studies did not perform a comparative analysis [13] or were unable to do so because of a 94% incidence of IUGR in their cohort [14].…”
Section: Discussionmentioning
confidence: 93%